If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6x + -2) = -476 Reorder the terms: 7(-2 + 6x) = -476 (-2 * 7 + 6x * 7) = -476 (-14 + 42x) = -476 Solving -14 + 42x = -476 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 42x = -476 + 14 Combine like terms: -14 + 14 = 0 0 + 42x = -476 + 14 42x = -476 + 14 Combine like terms: -476 + 14 = -462 42x = -462 Divide each side by '42'. x = -11 Simplifying x = -11
| 5(-8+7x)=-40 | | -5(-2x+4)=90 | | -5(1x+7)=-20 | | 2(1+1x)=24 | | 19/20*32 | | -5(2+7x)=-10 | | 3.14*4*1= | | 32*19/20 | | 15a^2+7ab-2b^2=0 | | 3x-3=-38-2x | | 4(3+3c)=56 | | 6(x+1)(x+1)-14=0 | | 10(x-2)=-2+40 | | 10+4x=7x+4 | | -12=-2x+3 | | 8+x=-4x-32 | | (5/7)=(x/21) | | 4y=-2x-1 | | 0.009/9 | | x+4=76-5x | | 33-x=33 | | 0.09/18 | | 7x-3=3x+41 | | 11(-5+4)= | | -y-7=-12 | | 576+100=x | | 2+6x+6x=26 | | Log(2)523=x | | -6+3x+6x=93 | | (-13)(-13)= | | 52=x+3x+4 | | 10x^3-70x^2+100x= |